Evaluation of physico-chemical quality crude oil almond babassu (Orbigny spp) - Oliveira, Lucillia Rabelo de; Neves, Josyanne Araújo; SILVA, Manoel de Jesus Marques da (Comunicata Scientiae, 2013)
The babassu palm (Orbignya spp) is important for the Northeast’s families survival, mainly in the states of Piauí and Maranhão, because of the exploration of its oil, the main byproduct. The objective of the current study was to evaluate the physical and chemical qualities of crude oil of the babassu almond produced in the agricultural zone of the Jose Freitas city, determining their oxidative status. Were collected in local market 10 samples of crude oil, chosen at random for realization of determinations, in triplicate, of the index of: peroxide, acidity, saponification value, refractive and density, according to the Standards of Adolph Lutz Institute (2005). In all the samples were not detected peroxides as products of oxidative processes, which indicates a good status of conservation of the oils investigated. One sample showed acidity value higher than the others, indicating possible hydrolytic rancidity, although the values to meet in accordance with standards. The saponification values of most samples were lower than recommended, while the refractive index and density were higher. According to the results, it was found that the oils evaluated were not within the established standards, except for the peroxide value and acidity, indicating inadequacies in quality of raw material for possible adulteration or inappropriates processing and storage of products or because they are species with distinct characteristics from those established as standards.